The Extension Mentor’s Discussion and Action Guide - Karlibeth Leitheiser; Matt Benge (EDIS, 2024)
Mentorship is a dynamic, developmental relationship between a mentor and a mentee (Kram, 1983). When the mentoring relationship is first established, it can be difficult to set norms and expectations for both parties. Mentor relationships should be established early in the mentee’s career, and the mentor relationship can benefit both the mentor and the mentee by providing a space for collaboration, learning, and support (Ragins, 1997). This publication provides a detailed discussion and action guide to help Extension mentors form and build their relationship with their mentee.